2021
DOI: 10.33545/26641291.2021.v3.i2b.76
|View full text |Cite
|
Sign up to set email alerts
|

The impact of handwashing guidelines on pediatric nurses' knowledge and practices in the operating room at Cairo University specialized pediatric hospital

Abstract: Pediatric nurses in the operating room are front-line heroes who save the lives of children by avoiding and preventing the infection by thoroughly washing their hands. The current study aimed to evaluate the impact of Handwashing guidelines on pediatric nurses' knowledge and practices in the operating room. Design: One group pre-posttest quasi-experimental research design was utilized to achieve the aim of the current study. Setting: The current study was conducted in the operating room at Cairo University Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…There was a statistically significant difference between the overall mean score of nurses' improper practices and the overall mean score of burn children's wound care practices. Ibrahim & Bahnsawy (2021), consistent with the current finding and concluded that handwashing and wearing full PPE are critical for reducing the occurrence of infections in all clinical settings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was a statistically significant difference between the overall mean score of nurses' improper practices and the overall mean score of burn children's wound care practices. Ibrahim & Bahnsawy (2021), consistent with the current finding and concluded that handwashing and wearing full PPE are critical for reducing the occurrence of infections in all clinical settings.…”
Section: Discussionsupporting
confidence: 92%
“…Based on Ebenezer et al, (2019) and Ibrahim & Bahnsawy (2021), the predominance of antibiotic resistance in burn infections necessitates the judicious use of antibiotics and strict infection control practices, such as frequent hand washing, avoiding sharing of equipment among patients, using barrier strategies, surgical removal, and closure of the wound, and using dermatologic antibiotics, improving the overall infection-related death and disability rates.…”
Section: Discussionmentioning
confidence: 99%